AN ECONOMIC STUDY OF BARLEY SUPPLY RESPONSE IN IRAQ FOR THE PERIOD 1980-2009 - Muhsen Awaid . Farhan; Sarah Ali Hussein; Zahra H. Mahmood (Mesopotamia Journal of Agriculture)
ABSTRACT Barley is one of the main crops in Iraq and is ranked the second most important crop after wheat. This study aimed to estimate supply response of planted acreage for barley in Iraq and irrigated and rained areas for the period from 1980 to 2009 using Nerlove dynamic model. Estimated results indicated that the main variables are lagged price of barley, lagged price of wheat, and lagged planted acreage for barely , besides irrigation water for Iraq and irrigated area, and risk factors of production for rained area .These variables represented about 82%, 87%, and 83% of the change in planted acreage for barley for Iraq, irrigated area, and rained area respectively . The own elasticities of barley with respect to its price for Iraq, irrigated area, and rained area were 0.046, 0.020, and 0.024 respectively. The cross elasticities of barley in respect to wheat price for Iraq and irrigated area were -0.115 and -0.229 respectively. The cross elasticities for barley in respect to legumes for irrigated area were -0.128 and -0.232 in the short-term and long-term respectively, whereas these elasticities in respect to vegetable price were -0.008 and -0.022 in the short-term and long-term respectively.